2002
DOI: 10.1016/s0022-5347(05)65181-6
|View full text |Cite
|
Sign up to set email alerts
|

The Patient With Chronic Epididymitis: Characterization Of An Enigmatic Syndrome

Abstract: This comprehensive clinical survey of men diagnosed with chronic epididymitis is the first step for defining and characterizing this particular population. Development of a classification system and symptom assessment index may direct further studies in the etiology, epidemiology and management of chronic epididymitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 7 publications
1
22
0
4
Order By: Relevance
“…The pain in our patients was severe, usually progressive, was worsened by even simple daily activity, and limited many of the activities of daily life like work, social activities, and sports. Many of the men were depressed and most felt that their condition was “terrible.” A similar finding was published by Nickel et al [9]. …”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The pain in our patients was severe, usually progressive, was worsened by even simple daily activity, and limited many of the activities of daily life like work, social activities, and sports. Many of the men were depressed and most felt that their condition was “terrible.” A similar finding was published by Nickel et al [9]. …”
Section: Resultssupporting
confidence: 91%
“…The impact of CSP on men's sexual and work activities was graded as none, only a little, some, or a lot using the published questionnaire from Nickel et al [9]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with an abnormal epididymis or vas deferens confirmed by palpation or direct echography, or presented pain or discomfort located at unilateral or bilateral scrotum, testicle or epididymis for previous 3 months or longer, were considered to have chronic epididymitis . Those chronic epididymitis patients usually presented indurations, irregularities, or thickening in the physical examination and reported a past event of scrotal pain episode related to genital infection or trauma.…”
Section: Methodsmentioning
confidence: 99%
“…Scores for this question were quantified on a linear scale from one to seven as 1 = delighted, 2 = pleased, 3 = mostly satisfied, 4 = mixed, 5 = mostly dissatisfied, 6 = unhappy, and 7 = terrible. 14 Earlier work by Andrews and Crandall 16 had suggested that a seven-point scale anchored with the words delighted and terrible was more sensitive and less negatively skewed than a five-point satisfaction scale for quality of life assessment, probably because it allowed for a broader range of affective responses to QOL items. 17…”
Section: Quality Of Lifementioning
confidence: 99%